NEW TECHNOLOGIES AND METHODS USED IN THE EDUCATION SYSTEM - Abdurаzzоqоv Ilhоm Rustamоvich; Xudoyberdiyev Nortura Kabilovich; Madayeva Muqaddas Baxtiyor qizi (Web of Journals Publishing, 2025)
New technologies and methods in the modern education system allow making the learning process interactive, effective and personalized. Artificial intelligence, virtual reality, online learning platforms, mobile applications, gamification and digital assessment tools deepen students' knowledge, develop independent learning skills and improve the quality of education.
Keywords: Artificial intelligence, digital education, online courses, virtual reality, blended learning, gamification, mobile applications, interactive whiteboards, e-learning, LMS, blended learning, video lessons, distance learning, EdTech, learning platforms, simulation, student-centered learning, personalization, cloud technologies, digital assessment, cognitive technologies, robotics, coding training, virtual laboratories, gamification, Big Data in education, voice assistants, AR, systematic analysis, smart classrooms.История развития информатики.